PENGEMBANGAN MODUL PEMBELAJARAN MATEMATIKA SISTEM PERSAMAAN LINEAR TIGA VARIABEL UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS - Waya, Henni Susilawati (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2022)
This research is motivated by students' low mathematical problem solving abilities, the center of mathematics learning in teacher-centered classrooms and teachers have not developed their own teaching materials in the form of modules. The purpose of this research is to develop teaching materials in the form of modules on the material of a three-variable linear equation system to improve students' mathematical problem solving abilities. The type of research used is Research and Development (R&D) with a 4D model (Define, Design, Development, Disseminate). Based on the results of research and discussion, the validity results were obtained based on the calculation results of the validation results from material experts and media experts with an average of 89, 55% and categorized as very valid. Practical results were obtained based on trials in limited classes and field classes. The average practicality result in the limited class trial is 4.4 with a percentage of 88.32% and is categorized as very practical, then the average practicality result in the field trial is 4.42 with a percentage of 88.32% and is categorized as very practical. Effectiveness results were obtained based on trials in limited classes and field classes. The results of the effectiveness of the limited class trial obtained an average of 0.62 with a percentage of 62.33% and were in the medium category. Field trials obtained an average of 0.61 percentage of 61.94% and were in the medium category. Thus, the results of the study indicate that the developed module has met the valid, practical and effective criteria. The developed module is expected to be used to support teaching and learning activities, especially in improving mathematical problem solving abilities.